PENGARUH METODE PEMBAYARAN COD DAN PAYLATER TERHADAP KEPUTUSAN PEMBELIAN PADA PLATFORM SHOPEE - Zulkarnain Siregar; Dina Aulia; Indah Permatasari Tambunan; Kharisma Nurbani; Marsela Natalie Hutapea; Rizky Idaman Telaumbanua; Rizky Ramadhan (Paulus Journal of Accounting (PJA), 2025)
This study aims to analyze the influence of Cash on Delivery (COD) and PayLater payment methods on purchase decisions on the Shopee platform among students of the Management Department, Faculty of Economics, Universitas Negeri Medan. Using a quantitative approach with 200 respondents selected through purposive sampling, data were collected via questionnaires and analyzed using multiple linear regression. The results show that both COD and PayLater have a significant partial and simultaneous effect on purchase decisions, with a significance value of 0.000 and a coefficient of determination (R²) of 0.431. This indicates that these two payment methods explain 43.1% of the variation in students’ purchase decisions on Shopee.